Protection of Human Rights from Sexual Violence Against Women and Children Victims in East Seram Regency (A Study of Court Decisions in 2018-2022) - Aritonang, Samuel Ivander; Susetyo, Heru (UNES Law Review, 2024)
This research discusses numerous cases of sexual violence in East Seram Regency based on court decisions from 2018–2022. The focus of this research is the protection and fulfillment of the right of sexual violence victims in East Seram Regency. This study is a normative juridical with analytical descriptive method based on theories, concepts and regulations which are analyzed qualitatively. The results of this study indicate that the protection and fulfillment of human rights of sexual violence victims in East Seram Regency is still suboptimal due to the existence of social factors in society that do not recognize the importance of protecting the rights of sexual violence victims. It is shown that a highly unhealthy patriarchal culture, a criminal justice system that does not fully advocate victims and still focuses on criminalizing the perpetrators, as well as a society with low educational and economic standards. The advice given is that it is necessary to provide advocacy to the public regarding healthy sex education and the delivery of the information regarding rights of women and children, to strengthen the capacity of law enforcement officials in protecting the rights of victims of sexual violence, and establishing implementing regulation for the Sexual Violence Criminal Act as a legal basis for providing protection for sexual violence victims.